Angiojet Thrombo-aspiration Guided by Trans-Oesophageal Ultrasound. (2016) - Holzer, T.; Durovray, J.-D.; Allain, E.; Corpataux, J.-M.
Abstract : Introduction: A 59 year old woman presented with acute right leg ischemia. On the computed tomography scan, thrombi were seen in the brachiocephalic trunk, in the descending aorta, in the infrarenal aorta, in the right deep femoral artery, and in the right crural arteries. Technique: To remove the risk of cerebral emboli, thrombo-aspiration of the brachiocephalic trunk was planned, with associated thrombectomy of the infrarenal aorta, the right deep femoral artery, and the right crural arteries. Because the brachiocephalic thrombus could not be visualized with angiography, the anesthetists, who were performing a trans-oesophageal ultrasound of the heart, were asked to locate the thrombus, which was easily seen on the trans-oesophageal ultrasound. The aspiration catheter Angiojet (Boston Scientific, Marlborough, MA, USA) could be positioned under ultrasound guidance. Complete aspiration of the thrombus was then confirmed with the ultrasound (see video). The thrombectomy of the infrarenal aorta and right leg was then performed by open surgery. The patient's recovery was uneventful. Despite extensive investigations no etiology was found for the thrombi. Discussion: Pre-operative trans-oesophageal ultrasound is routinely performed by anesthetists in patients with acute ischemia, to search for a cardiac source of emboli. In this case it had the added advantage of helping to locate and aspirate a thrombus in the brachiocephalic trunk.